ANALISIS PEMBERIAN KOMPENSASI KEPADA KARYAWAN PADA PT. AGUNG AUTOMALL JAMBI - Hanibal Putra (Jurnal Dinamika Manajemen, 2015)
The purpose of this research is to describe and analyze the provision of compensation at PT. Agung Automall Jambi. The method used in this research is descriptive analysis, the method of collecting data through literature, interviews and questionnaires and the analysis used is simple tabulation analysis, where the measurements are carried out by knowing employee responses based on each respondent's answer to the statement submitted and given a weighted value. After that, a rating scale range was used to determine the position of the respondent's response using the score for each aspect. From the results of the study it can be concluded that employee responses to the implementation of the award compensation for PT. Agung Automall employees as a whole for the four aspects of compensation, namely salary, wages, incentives and indirect compensation is very adequate. The compensation given to employees is in the form of basic salary, overtime pay, meal allowance, health allowance, social security, day Raya, social security, bonuses and awards. While the compensation payment system used is a time system. Based on this research, suggestions can be put forward to the company's management that the company must pay more attention to the compensation provided, especially in the aspect of wages for the future it must be improved again without putting aside other aspects and For the future LTO must also be considered to be even better by increasing the amount of compensation given to employees from year to year so that employees can stay working at the company, so that the number of employees who leave will certainly decrease.